Influence of cement materials - Rosato, Vilma (2013)
There is scarce information about biological colonization of dams. However, like any other structure, they are subjected to the action of different organisms. In this study, dams, lichens, bryophytes and diatoms have been observed, and it has been noticed that their abundance and distribution is related to the climate conditions and the relative position of the water level. Besides, little is known about the influence of the cement composition on the growth of these organisms, which is important because of the current use of cements with different additions. In order to answer this question, tests have been done using a non lichenized fungus, namely Aspergillus niger, because lichen mycobionts grow very slowly in the culture.